MUTAGENESIS IN MICROSPORE CULTURE OF BRASSICA NAPUS - Zhambakin , K.Zh.; Zatybekov , A.K.; Volkov , D.V.; Shamekova , M.Kh. (Eurasian Journal of Applied Biotechnology, 2015)
The influence of chemical mutagens on a culture of isolated microspores of oilseed rape, Brassica napus, was studied. Microspores and the embrioids derived from them were subjected to mutagenesis. It was observed that the mutagens sodium azide (NaN3) and ethylmethanesulfonate significantly influenced the induction of embryogenesis within an hour of application to isolated microspores. When compared to the control group, the lines with a higher seed weight and a weight of 1000 seeds could be isolated from the plant material. The best results were observed by the lines that were obtained with 25mM NaN3 after a 4-hour exposure. There is a significant increase of oleic acid levels due to the decrease in concentration of linoleic acid in the first mutant generation. A significant drop in oleic acid content is seen in all cultured lines in the second generation M2, with oleic acid levels being higher in the first generation M1. At the same time, linoleic acid levels are increased in those lines. Dwarf and ripening forms was observed during the process of growth and development of plants in the field conditions. Most of the obtained mutant strains were sterile. We also observed an average decrease in the unsaturated fatty acid content in the mutants of the second generation. Mutant double haploids with signs of high productivity and high quality of seed oil were obtained in this study.